Fusing the Fictional and the Real in the Contemporary Performing Arts: Projects by the via Negativa Group - Orel, Barbara (Nordic Theatre Studies, 2018)
The exploration of the relationship between the fictional and the real in projects by Via Negativa, a performance group from Slovenia, is based on the presumption that the recognition of what we experience as fictional or real is decisively influenced by the perceptual activity of the spectator. The article argues that the exchange between the elements of fiction and reality takes place in two different concepts of representation: theatricality and absorption. These are two opposing notions used for defining the relationship between the image represented and the spectator. Theatricality is the effect of the address that the image makes to the spectators and thus makes them conscious of their own act of perceiving. Absorption, in turn, describes the context in which the image is put to view as a closed, self-sufficient sign-system establishing such conditions of perception that make the spectator focus completely upon the object represented; the audience is so overcome by the presented image that they experience this as if they were absorbed into the staged world. These two concepts are elaborated on the basis of Denis Diderot's essays on theatre and fine art. The essay proves useful for the argumentation of the thesis since they testify that theatricality and absorption, each in their own way, include the spectator's personal investment into what comes across as fictional or real. A detailed analysis of selected performances by Via Negativa shows that the real assuch (i.e. theauthenticity of the real that isconfirmed in the identity with its own self) is impossible to achieve. Under the gazeof the spectator, the real is always compelled to reveal itself through some kind of representation. As also found by Alain Badiou, the authenticity of the real can only be presented through the role of semblance, mask or fiction.